MRT-7 Araneta Station land and rail intermodal terminal - Almero, Katherine L.
Transport is an important part of our daily activities and a big concern to the public commuter. It requires more time with the transfers between modes of transportation, especially in the Philippines. In our current transport architecture, an easy transfer is uncommon. Instead it requires more effort and energy. Terminals are separated far from each other and requires passing through unmaintained and not-user friendly pathway connections. With the development of an intermodal station, the travel experience of public commuters can be made more convenient by making the transfer between modes of transportation easier. This is possible by linking the transportation modes in one development. The MRT-7 Araneta Station is one of the few intermodal stations to be developed in the country. The MRT Araneta Station aims to alleviate the public commuting experience by putting emphasis on the provision of a comfortable and convenient design for both passengers and drivers through (1) efficient flow of transfer between public transportations, (2) easy way finding from simple layout spaces, (3) less transfer time by reducing distance between transportations, and (4) reduced vehicular confusion with segregated spaces. The station uses the concept of Integrated Bridging to link the community and the transportation system through the structure and its public space - roof garden. This allows the station to enter the urban fabric as a landmark from its civic use and environment inspired form. By considering both the station's main users and its neighborhood, the project is able to create an intermodal station that connects not only people but also the city to transportation system. A landmark that is both a gateway and a city square.